2019
DOI: 10.1136/vr.104784
|View full text |Cite
|
Sign up to set email alerts
|

Porcine circovirus type 3 detection in a Hungarian pig farm experiencing reproductive failures

Abstract: Porcine circovirus 3 (PCV3) infection has been reported in piglets and sows with porcine dermatitis and nephropathy syndrome, reproductive failure, and cardiac and multisystemic inflammation. Few studies linked PCV3 infection to increased incidence of abortion and weak-born piglets. This is the first report of a detection of PCV3 Hungarian strain in several organs of aborted and weak-born piglets, including the thymus, lymph node, placenta, spleen, kidney and the liver. The tissue tropism of PCV3 in affected l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 15 publications
4
38
0
Order By: Relevance
“…Subsequently, this virus has been detected by molecular methods in pigs displaying a number of different conditions such as porcine dermatitis and nephropathy syndrome (PDNS) (Arruda et al, 2019;Palinski et al, 2017), respiratory disease (Kedkovid et al, 2018;Qi et al, 2019;Shen et al, 2018;Zhai et al, 2017), enteric disease (Qi et al, 2019;Zhai et al, 2017), reproductive problems (Arruda et al, 2019;Deim et al, 2019;Faccini et al, 2017), multisystemic affection (Phan et al, 2016) and in healthy animals Stadejek, Woźniak, Miłek, & Biernacka, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, this virus has been detected by molecular methods in pigs displaying a number of different conditions such as porcine dermatitis and nephropathy syndrome (PDNS) (Arruda et al, 2019;Palinski et al, 2017), respiratory disease (Kedkovid et al, 2018;Qi et al, 2019;Shen et al, 2018;Zhai et al, 2017), enteric disease (Qi et al, 2019;Zhai et al, 2017), reproductive problems (Arruda et al, 2019;Deim et al, 2019;Faccini et al, 2017), multisystemic affection (Phan et al, 2016) and in healthy animals Stadejek, Woźniak, Miłek, & Biernacka, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a novel and genetically divergent circovirus, PCV3, was found in swine with PDNS, PMWS in the United States (Palinski et al, 2017). Subsequently, this virus has been detected in many countries and has an abnormally high positive rate (Costa et al, 2014;Deim et al, 2019;Faccini et al, 2017;Saraiva et al, 2019). In China, multiple epidemiological surveillance data indicated that this virus was extensively prevalent in pigs in many provinces and specific cities (Qi et al, 2019;Sun et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In one study from South Korea, the virus was suggested as the potential cause of an increased abortion and death rates of suckling piglets, since they could not demonstrate evidence of another pathogen in the tested animals [ 13 ]. A Hungarian newly populated farm experienced an increase of abortions and acute losses of neonatal piglets from the primiparous sows as well as an increase of stillborn and mummified fetuses compared to previous cycles; PCV-3 was the only pathogen found in these cases [ 12 ]. However, the most unequivocal association to date of PCV-3 association with reproductive disease has been reported from the USA [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in such scenarios, it is important to elucidate to which extent and in which frequency PCV-3 does circulate in normally performing farms. In fact, most of these studies reporting an association between PCV-3 and reproductive losses lack proper negative controls with standard reproductive parameters [ 12 , 13 , 16 , 22 ]. Therefore, the aim of the present study was to evaluate the frequency of PCV-3 in samples from farms with good reproductive parameters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation